2017
DOI: 10.1108/el-10-2016-0228
|View full text |Cite
|
Sign up to set email alerts
|

Measuring global research activities using geographic data of scholarly article visits

Abstract: Purpose This study aims to analyse the geographical distribution of global research activities and to investigate the knowledge diffusion embodied in scientific papers. Design/methodology/approach The geographical summary of Frontiers articles displays the number of visits and categorizes where the visitors hail from. This study uses the records of 23,798 articles published in 16 Frontiers journals from 2007 to 2015 to analyse the geographical distribution of article visits at both country and city levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The entire process of scientific and technological innovation involves ongoing research activity. Due to the lack of previously conducted research-related data, it is challenging to measure and track the research activities in a timely manner (Fang et al, 2017). A study by Barney et al (2022) on the research, balance and teaching levels of 324 management faculty members at public universities in the USA found that no one job resource accurately predicted the research output for all of the participants.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The entire process of scientific and technological innovation involves ongoing research activity. Due to the lack of previously conducted research-related data, it is challenging to measure and track the research activities in a timely manner (Fang et al, 2017). A study by Barney et al (2022) on the research, balance and teaching levels of 324 management faculty members at public universities in the USA found that no one job resource accurately predicted the research output for all of the participants.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The entire process of scientific and technological innovation involves ongoing research activity. Due to the lack of previously conducted research-related data, it is challenging to measure and track the research activities in a timely manner (Fang et al. , 2017).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The GIS using structures that show probable strategies to loyalty card data analysis and place loyalty card data in the hierarchy of an organization (Byrom et al , 2001). Fang et al (2017) evaluate how worldwide research operations and pursuits are transmitted in disseminating new knowledge in scientific publications. In addition to geographic search, the GIS interface improves community-level services among society’s users.…”
Section: Review Of Literaturementioning
confidence: 99%
“… 18 These metrics can be monitored over time to visualize temporal and geographic trends of article usage. 19 20 Variations in use of HTML, PDF, and XML article formats can be also reported to guide publishers over the readership preferences and priorities for reuse, archiving, and marketing. 19 …”
Section: Views and Downloadsmentioning
confidence: 99%